2017
DOI: 10.18632/oncotarget.17162
|View full text |Cite
|
Sign up to set email alerts
|

New tumor suppressor microRNAs target glypican-3 in human liver cancer

Abstract: Glypican-3 (GPC3) is an oncogene, frequently upregulated in liver malignancies such as hepatocellular carcinoma (HCC) and hepatoblastoma and constitutes a potential molecular target for therapy in liver cancer. Using a functional screening system, we identified 10 new microRNAs controlling GPC3 expression in malignant liver cells, five of them e.g. miR-4510, miR-203a-3p, miR-548aa, miR-376b-3p and miR-548v reduce GPC3 expression. These 5 microRNAs were significantly downregulated in tumoral compared to non-tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…miR-203a-3p in liver cancer and bladder cancer was up-regulated [33, 34], and the expression of other miR-203 family members could be up-regulated in cervical cells [35]. Other studies have shown that the expression of miR-203a-3p was down-regulated in nasopharyngeal carcinoma [23].…”
Section: Discussionmentioning
confidence: 99%
“…miR-203a-3p in liver cancer and bladder cancer was up-regulated [33, 34], and the expression of other miR-203 family members could be up-regulated in cervical cells [35]. Other studies have shown that the expression of miR-203a-3p was down-regulated in nasopharyngeal carcinoma [23].…”
Section: Discussionmentioning
confidence: 99%
“…Primer efficiency was between 95% and 105%. miR-4510 expression was measured as described before [2].…”
mentioning
confidence: 99%
“…Total RNA was extracted from cultured cells using Trizol (Sigma, St Louis, MO, USA) reagent or mirVana miRNA Isolation Kit (Life Technologies, Carlsbad, CA, USA) according to the manufacturer's instructions. miR-4510 expression was measured as described previously[2]. To quantify mRNA expression, complementary DNA was synthesized with the Maxima Reverse Transcriptase kit (Thermo…”
mentioning
confidence: 99%
“…To our knowledge, only one report about miR‐4510 function has been found. This finding identifies miR‐4510 as a suppressor in liver cancer by targeting glypican‐3 (Cartier et al, 2017). Conformably, our results suggested that miR‐4510 served as a suppressor in GIST cells.…”
Section: Discussionmentioning
confidence: 97%